PENDAMPINGAN PENGELOLAAN KEUANGAN KOMUNITAS “POMP SEMBADA SLEMAN” - Anggraini, Francisca Reni Retno; Suryandari, Ilsa Haruti; Sulistiyowati, Firma (Universitas Sanata Dharma, 2023)
This community service aims to help improve the empowerment of the Merpati Pos Sports Association (POMP) community in Sleman Regency, known as Sembada Sleman POMP through mentoring on good financial management. The implementation of the activity begins with (1) identifying and understanding the business processes that exist in this community, (2) the practice of financial recording that has been carried out so far, (3) evaluating the process of financial recording and the use of financial information as a basis for evaluation and planning, and (4) recommendations in the form of SOP proposals for financial records and the use of financial information as a basis for evaluation and planning activities. The results achieved from this community service are to develop Excel software for the SEMBADA SLEMAN POMP community so that they can make financial reports quickly and accountably and use financial information as material for evaluation and activity planning. The recommendation for the SEMBADA SLEMAN POMP community is to use the software in compiling financial reports. Servants will always be ready to assist when experiencing difficulties.